Sirenomelia with associated systemic anomalies – an autopsy report in a full term neonate - Alina, Vesa; Maghiar, Octavian; Cuc, Romina; Popescu, Elena; Dorobantu, Ramona; Maghiar, Laura; Pop, Ovidiu; Boros, Monica (Polish Journal of Pathology, 2022)
The mermaid syndrome, also known as sirenomelia, is considered an extremely rare congenital developmental disorder characterized by anomalies of the lower spine and lower limbs. Affected babies are born with partial or total leg fusion. Sirenomelia is thought to affect one in every 60,000 to 100,000 infants. We report a case of sirenomelia occurring in a 28-year-old multiparous woman, a heavy smoker with gestational diabetes. In the other 5 pregnancies, however, she gave birth to normal babies. The post mortem examination completed the diagnosis, revealing also multiple malformations of several systems: respiratory, gastro-intestinal, genito-urinary and cardiovascular. In our full term neonate case with grade VI sirenomelia, the presence of a single umbilical artery plus the abdominal aorta with an aberrant trajectory that ends in the umbilical cord differentiates this condition from caudal regression syndrome and also explains the under-development of pelvic organs (secondary to vascular steal phenomena).